Perancangan Dan Pengujian Alat Pemasak Energi Surya Photovoltaic Kapasitas 2 Liter - Perangin-angin, Siwan Ediamanta (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2025)
The design of this solar cooker aims to utilize solar radiation as an energy source, in cooking ingredients such as indomie and 2 liters of water. To reduce the use of fossil fuels which is increasing day by day. Testing of this solar cooker was carried out on the roof of the Faculty of Mechanical Engineering building, HKBP Nommensen University, Medan. This solar cooker is intended for use by one family and is expected to be used in rural areas where electricity cannot reach. This design is a quantitative research, which calculates the power and capacity of the tool components to be designed by looking at previously existing journals. Equipment testing was carried out to find out how much power and time is needed to cook ingredients such as indomie and water with a capacity of 2 liters. Testing was carried out from 08.00 WIB to 16.00 WIB under sunlight. The conclusion from the design and testing of the Photovoltaic solar cooker is: the efficiency for cooking indomie with one liter of water is 93% and the efficiency for cooking two liters of water is 48%.